Integrating Adab and Prophetic Paradigms: Reconstructing Islamic Education through Al-Attas and Kuntowijoyo - Fahri Hidayat (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
Contemporary developments in the philosophy of Islamic education reveal an ongoing debate between the paradigm of the Islamization of Knowledge, which emphasizes the formation of Islamic identity, and the need to transform Islamic values into the plural public sphere. Syed Muhammad Naquib al-Attas's paradigm of the Islamization of Knowledge has successfully established the metaphysical and epistemological foundations of Islamic education through the concept of ta'dib. However, it still faces challenges in explaining how revelatory values can be translated into diverse fields of knowledge and universally applicable social realities. In contrast, Kuntowijoyo's paradigm of objectification provides a mechanism for transforming Islamic values into inclusive scientific and social categories. This study aims to reconstruct the philosophy of Islamic education through a critical dialogue between Al-Attas's concept of ta'dib and Kuntowijoyo's paradigm of objectification. Employing a qualitative library research design with a comparative-critical philosophical approach, the study analyzes the primary works of both scholars alongside relevant contemporary academic literature through qualitative content analysis and conceptual synthesis. The findings demonstrate that the integration of these two paradigms produces a model termed Prophetic-Adabic Islamic Education, which integrates the cultivation of adab, the objectification of Qur'anic values, and the development of knowledge. The proposed model provides a philosophical foundation for strengthening character education and developing an integrated curriculum that bridges Islamic and modern sciences, enabling Islamic education to produce graduates who possess moral integrity, intellectual excellence, and the capacity to advance knowledge for the promotion of public benefit (maṣlaḥah).